An Investigation Of The Non-Metallic Mineral Industry In Companies Admitted Into Tehran Exchange Market By Using Financial Ratios - Shojaeddin, Arash (2009)
The most important goal of this research project is to amend and apply Altman's bankruptcy prediction model in companies admitted in to Tehran's exchange market in Non-metallic mineral industry.